Evaluasi Pelaksanaan Training Instructor Course (TIC) Di Pusat Pengembangan Sumber Daya Manusia Perhubungan Udara - I Gusti Agung Ayu Mas Oka; Syukri Hamzah; Hadi Winata; I M. Bayu Astika (Politeknik Penerbangan Indonesia Curug, 2023)
This study aims to evaluate the implementation of the Training Instructor Course (TIC) at the Centre of Human Resources Development on Civil Aviation (CHRDCA) using the Kirkpatrick model. TIC training was developed and standardized by the International Civil Aviation Organization (ICAO). ICAO has developed level 1, 2 and 3 evaluations for TIC training, but has not yet developed level 4 evaluations. CHRDCA can access evaluation levels 1 and 2 from the Trainair Plus Electronic Management System (TPEMS). The evaluation results at level 1 were very good with an average score of 4.73. The results of the level 2 evaluation showed that all participants passed with an average score of 87.1. Level 3 evaluation results are managed directly by ICAO so CHRDCA cannot access them. However, the researchers conducted a survey with the results showing that there was an increase in the quality of behaviours in managing learning. Based on the results of the evaluation at level 3, it can be concluded that at evaluation level 4 there will be an increase in student learning results as a result of an increase in the instructor's pedagogical competence.